The Effect Self-Confident on Mathematical Creativity - Setiawan, Yayan Eryk (Universitas Muhammadiyah Surakarta, 2023)
One of the important things to note in supporting the success of learning is self-confidence and creativity. The purpose of this study was to determine the effect of self-confidence on mathematical creativity. This type of research is quantitative research. Through the use of random sampling techniques, the sample for this study was 65 semester 1 student in the mathematics education study program at the Islamic University of Malang. The data collected in this study is the result of a questionnaire about students' self-confidence and mathematical creativity. The questionnaire used in this study has met the validity and reliability. Questionnaire results were analyzed by correlation test and linear regression test. Correlation and linear regression tests were carried out with the help of SPSS. The results of the research show that there is a correlation between self-confidence and mathematical creativity. The results also show that self-confidence has a positive effect on mathematical creativity by 32.5%. This influence is due to four things, namely self-confidence in solving math problems (even though it is difficult), confidence in expressing opinions during discussions, confidence when appearing in front of the class, and confidence when answering questions from the teacher. Thus, it is important to train students to be more confident in solving math problems, so that this will increase their creativity in solving math problems.